Sort it out! - Lee, Yee Ching. (2009)
Sort it out! is an environmental campaign aiming to create awareness about Singaporeans’ excessive consumption and waste disposal habits. The target audience are the teenagers and young adults from age 13–25 years old. Teenagers and young adults, being apathetic, may not have the sense of responsibility for the environment. Most people find sorting out their rubbish a chore and troublesome. This campaign hopes to encourage the youths and young adults to sort out their rubbish whether it is the recyclables (putting them in the recycling bins according to their categories) or reusing items. For the environment, it is worth the effort and time.